1994
DOI: 10.1021/bi00200a034
|View full text |Cite
|
Sign up to set email alerts
|

Core Antenna Complexes, CP43 and CP47, of Higher Plant Photosystem II. Spectral Properties, Pigment Stoichiometry, and Amino Acid Composition

Abstract: The core antenna complexes of photosystem II, CP43 and CP47, were purified from two higher plants by anion-exchange chromatography, using a combination of the chaotropic agent UCIO4 and the nonionic detergent /3-dodecyl maltoside. The Qy transition was resolved at 48 K into two main bands near 682.3 and 671.5 nm for CP43, while the CP47 spectrum showed a more complex structure with main bands at 688, 681.2, 676, 670, 667, and 661 nm. Emission bands (77 K) were detected at 683 and 695 nm for CP43 and CP47, resp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(113 citation statements)
references
References 34 publications
10
101
2
Order By: Relevance
“…However, 77K fluorescence emission data indicate that the LHCII complexes present in ac29 are attached to PSII RCC complexes in vivo. PSII displays two fluorescence emission peaks at 695 nm and 686 nm corresponding to CP47 and CP43, respectively (Alfonso et al, 1994;Shen and Vermaas, 1994). In ac29, the CP47 peak was significantly higher as compared with the CP43 peak than in the wild type, indicating a higher energy transfer to CP47 than to CP43 and attachment of a higher number of antennae proteins to CP47 than to CP43.…”
Section: Discussionmentioning
confidence: 99%
“…However, 77K fluorescence emission data indicate that the LHCII complexes present in ac29 are attached to PSII RCC complexes in vivo. PSII displays two fluorescence emission peaks at 695 nm and 686 nm corresponding to CP47 and CP43, respectively (Alfonso et al, 1994;Shen and Vermaas, 1994). In ac29, the CP47 peak was significantly higher as compared with the CP43 peak than in the wild type, indicating a higher energy transfer to CP47 than to CP43 and attachment of a higher number of antennae proteins to CP47 than to CP43.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of the ellipticity peak of the ␤-carotene at 457 nm to that of the Chl a at 670 nm is 4.6:1. This ratio in the CP43 light-harvesting complex, which contains chlorophyll a and ␤-carotene in a ratio of 4:1, is 1:1 ␤-Carotene in Cytochrome b 6 f Complex (28). It is concluded that all of the bound ␤-carotene is bound in the complex in an asymmetric environment.…”
Section: Characterization Of the Cytochrome Bmentioning
confidence: 91%
“…The core complexes of photosystems I and II contain P700-chlorophyll a-protein complex and CP43/CP47 as internal light-harvesting antenna, respectively, and these complexes contain chlorophyll a and b-carotene as the photosynthetic pigments (Alfonso et al, 1994;Ben-Shem et al, 2003). On the other hand, depending on the photosynthetic organism, peripheral antenna complexes contain a variety of pigments, such as phycobilins, chlorophyll b, and fucoxanthin (Green and Durnford, 1996;Ting et al, 2002).…”
Section: Introductionmentioning
confidence: 99%